Conducting ion / conducting ion and electron asymmetric solid-state electrolyte membrane, preparation method thereof and solid-state lithium metal battery

By adopting an asymmetric solid electrolyte membrane in solid-state lithium-ion batteries, conducting ions to the positive electrode side, and ions and electrons to the negative electrode side, and inducing directional deposition of lithium ions, the low ion conductivity and lithium dendrites of solid-state lithium-ion batteries are solved, achieving higher electrochemical performance.

CN119560628APending Publication Date: 2025-03-04DALIAN UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411734918.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Solid-state lithium-ion batteries have low room temperature ion conductivity and lithium dendrites growth problems, and the solid/solid interface between the solid electrolyte and the electrode cannot be fully fit, resulting in poor contact.

Method used

An asymmetric solid electrolyte membrane that conducts ions/conducts ions and electrons is adopted. The membrane conducts ions on the positive electrode side and ions on the negative electrode side, and forms a lithium metal layer connecting the electrolyte membrane and the lithium negative electrode to improve interface contact by inducing directional deposition of lithium ions.

Benefits of technology

The uniform deposition of lithium ions is achieved, the ionic conductivity of the solid electrolyte membrane is improved, the problem of lithium dendrites is alleviated, and the electrochemical performance of solid lithium metal batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560628A_ABST
    Figure CN119560628A_ABST
Patent Text Reader

Abstract

The invention discloses an asymmetric solid electrolyte membrane for conducting ions / conducting ions and electrons, a preparation method of the asymmetric solid electrolyte membrane and a solid lithium metal battery. The asymmetric solid-state electrolyte membrane comprises an ion-conducting electrolyte facing the positive electrode side, and comprises an ion-conducting and electron-conducting electrolyte added with an electron-conducting material facing the negative electrode side. The ionic conductivity of the asymmetric solid electrolyte membrane at 30 DEG C is gt; 3mS cm <-1 >. And under the current density of 0.2 mA cm <-2 >, the lithium symmetric battery stably operates for more than 660 hours. The capacity of the solid-state LiFePO4 | | Li battery after 650 times of circulation is kept to be 100 mA h g <-1 > or above under the multiplying power of 0.5 C, and the capacity retention ratio is 70% or above. The asymmetric solid electrolyte membrane disclosed by the invention is high in ionic conductivity, lithium ions are induced to deposit in a membrane for guiding ions and electrons facing a lithium negative electrode side and a negative electrode interface, and the electrochemical performance of a solid lithium metal battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolyte membrane lithium metal batteries, and in particular to an asymmetric solid electrolyte membrane that conducts ions / conducts ions and electrons, a preparation method thereof, and a solid lithium metal battery, wherein the solid lithium metal battery is assembled from the solid electrolyte membrane. Background Art

[0002] With the development of economy, the progress of science and technology, and the growth of population, the importance of energy has become more and more prominent. At present, traditional fossil fuels are non-renewable and accompanied by environmental pollution problems. The development of new clean energy is urgent. In order to improve the utilization of energy, batteries as energy storage and conversion devices have attracted attention. Lithium-ion batteries have the advantages of high energy density, long cycle life, and high operating voltage. They have received more and more attention and have been widely used in portable electronic products, electric vehicles and other fields. However, traditional lithium-ion batteries still have safety problems such as easy leakage, volatility, and flammability of electrolytes. The energy density is also about to reach the theoretical upper limit, and it is necessary to develop safer and higher energy density batteries. Solid-state lithium-ion batteries have higher safety and energy density and have good development prospects.

[0003] Solid-state lithium-ion batteries have the problems of low room temperature ionic conductivity of the solid electrolyte membrane and lithium dendrite growth. In addition, the solid electrolyte and the electrode are both solid, and the solid phase interface cannot be completely fitted. It is a point contact of the solid / solid interface with poor interface contact. As the core of solid-state lithium-ion batteries, the solid electrolyte membrane is the key to solving these problems. The research and development of new solid electrolyte membranes with both high ionic conductivity and the ability to inhibit lithium dendrites is of great significance to improving the comprehensive performance of solid-state lithium-ion batteries. Summary of the invention

[0004] The object of the present invention is to provide an asymmetric solid electrolyte membrane that conducts ions / conducts ions and electrons, and the electrolyte membrane conducts ions facing the positive electrode side, conducts ions and electrons facing the negative electrode side, and simultaneously induces lithium ions to be directional deposited in the side membrane and the negative electrode interface, forming a lithium metal layer connecting the electrolyte membrane and the lithium negative electrode, achieving uniform deposition of lithium ions and alleviating the poor solid / solid interface contact between the solid electrolyte and the electrode. The solid electrolyte membrane includes an ion-conducting electrolyte facing the positive electrode side, and an electrolyte that conducts ions and electrons while adding an electronic conductive material facing the negative electrode side.

[0005] The second purpose of the present invention is to provide a method for preparing an asymmetric solid electrolyte membrane that conducts ions / conducts ions and electrons. An asymmetric base membrane containing a conductive material facing the lithium metal side is obtained by electrostatic spinning, electrostatic spraying or magnetron sputtering, and then an asymmetric solid electrolyte membrane is obtained by in-situ polymerization. This method is simple, easy to scale up and can be used for large-scale production; the electrolyte facing the positive electrode side can also be obtained by one or more methods of solution casting, scraping, rolling and additive manufacturing, and then the electrolyte with added conductive material facing the negative electrode side is obtained by one or more methods of solution casting, scraping, rolling and additive manufacturing on the positive electrode side electrolyte.

[0006] The third object of the present invention is to provide a solid-state lithium metal battery based on the above-mentioned asymmetric solid electrolyte membrane to improve the electrochemical performance of the battery.

[0007] To achieve the above objectives, the present invention provides the following technical solutions:

[0008] An asymmetric solid electrolyte membrane that conducts ions / conducts ions and electrons, comprising an ion-conducting electrolyte on the side facing the positive electrode and an electrolyte that conducts ions and electrons while adding an electronic conductive material on the side facing the negative electrode.

[0009] Furthermore, the conductive material includes one or more of carbon nanotubes, silver nanowires, silver nanoparticles, copper nanowires, copper particles and silver-copper alloys.

[0010] Furthermore, the asymmetric solid electrolyte membrane comprises an asymmetric base membrane, wherein the side of the asymmetric base membrane facing the positive electrode comprises a polymer or an electrolyte, and the side facing the lithium metal negative electrode comprises a mixture of a conductive material and a polymer or a conductive material; the asymmetric base membrane is filled with a polymer electrolyte, and the polymer electrolyte contains a plasticizer and a lithium salt. The asymmetric solid electrolyte membrane conducts ions facing the positive electrode side, conducts ions and electrons facing the negative electrode side, and simultaneously induces lithium ions to be directional deposited in the side membrane and at the interface with the lithium metal negative electrode, forming a lithium metal layer connecting the electrolyte membrane and the lithium negative electrode, achieving uniform deposition of lithium ions and improving the problem of lithium dendrite growth.

[0011] Furthermore, the mass ratio of the electronic conductive material to the polymer on the side of the asymmetric base membrane facing the lithium metal negative electrode is 0.0001:1 to 1:0, preferably 0.1:1 to 1:0.

[0012] Furthermore, in the asymmetric base membrane, the polymer is a polymer for preparing the base membrane, including one or more of polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, polyimide, polyetherimide, polyvinyl alcohol, polyvinyl pyrrolidone, polymethyl methacrylate and polyvinyl chloride.

[0013] Furthermore, the polymer electrolyte is obtained by polymerizing a polymer monomer that conducts lithium ions and mixes a plasticizer and a dissolved lithium salt.

[0014] Furthermore, the plasticizer includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, succinonitrile and fluoroacetonitrile; the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium difluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium dioxalatoborate and lithium difluorooxalatoborate; the polymer monomer includes one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, vinylene carbonate, polyethylene glycol methyl ether methacrylate, tetrahydrofuran and 1,3-dioxolane.

[0015] The present invention also provides a method for preparing the asymmetric solid electrolyte membrane that conducts ions / conducts ions and electrons, wherein the electrolyte facing the positive electrode side is obtained by one or more methods selected from solution casting, scraping, rolling and additive manufacturing, and then the electrolyte with added conductive material facing the negative electrode side is obtained on the positive electrode side electrolyte by one or more methods selected from solution casting, scraping, rolling and additive manufacturing.

[0016] The present invention also provides a method for preparing the ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane, comprising the following steps:

[0017] (1) Preparation of asymmetric base membrane

[0018] The conductive material, polymer and solvent are heated, mixed and stirred to form a uniform and viscous spinning solution, and electrostatic spinning is performed on the polymer membrane or electrolyte membrane to obtain an asymmetric base membrane with single-side conductivity; or a conductive material is electrosprayed on one side of the polymer membrane or electrolyte membrane by electrostatic spraying or magnetron sputtering to obtain an asymmetric base membrane with single-side conductivity;

[0019] (2) Preparation of asymmetric solid electrolyte membrane

[0020] The lithium salt is dissolved in the polymer monomer and the plasticizer, and the polymerization initiator is added and stirred evenly, and then the mixture is dripped onto the asymmetric base membrane prepared in step (1), and then the base membrane is transferred into an oven for heating and polymerization to obtain an asymmetric solid electrolyte membrane.

[0021] Furthermore, in step (1), the solvent is a solvent that dissolves the polymer, including N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, water, ethanol, acetone, toluene, xylene, chloroform, dichloromethane or dimethyl sulfoxide.

[0022] Furthermore, the mass percentage of the conductive material in the spinning solution, the electrostatic spray solution or the electrolyte facing the negative electrode side is 0.1% to 99.9%.

[0023] Furthermore, the polymer membrane is obtained by electrospinning or phase inversion, and the mass percentage of the polymer in the membrane liquid is 1% to 50%; the electrolyte membrane is obtained by one or more methods of solution casting, scraping, rolling and additive manufacturing.

[0024] Furthermore, in step (1), the mixing and stirring time is 1 to 48 hours, and the heating temperature is 30 to 100°C.

[0025] Furthermore, in step (1), the voltage of the electrospinning is 5 to 50 kV, and the spinning speed is 0.001 to 10 mL min -1 , the receiving distance is 0.5cm~80cm.

[0026] Furthermore, in step (2), the mass ratio of the polymer monomer to the lithium salt is 0.01:1 to 100:1.

[0027] Furthermore, in step (2), the mass ratio of the plasticizer to the polymer monomer is 0.001:1 to 100:1.

[0028] Furthermore, in step (2), the mass of the polymerization initiator is 0.01 to 100% of the mass of the polymer monomer.

[0029] Furthermore, the polymerization initiator in step (2) includes one or more of 2,2-azobisisobutyronitrile, dibenzoyl peroxide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), boron trifluoride and aluminum trifluoromethanesulfonate.

[0030] Furthermore, in step (2), the stirring time is 1 to 48 hours.

[0031] Furthermore, in step (2), the polymerization temperature is 20 to 200° C., and the polymerization time is 0.01 to 48 hours.

[0032] The present invention also provides a solid-state lithium metal battery, comprising a positive electrode, a negative electrode and a solid-state electrolyte membrane, wherein the solid-state electrolyte membrane is the ion-conducting / ion-and-electron-conducting asymmetric solid-state electrolyte membrane.

[0033] Furthermore, the positive electrode is lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.

[0034] The beneficial effects of the present invention include:

[0035] The asymmetric solid electrolyte membrane of the present invention has excellent ion conductivity (>3mS cm -1 ), which contains electronic conductive material on the side facing the lithium metal negative electrode. The conductive ions and electrons can simultaneously induce lithium ions to be directional deposited in the side film and at the interface with the negative electrode, forming a lithium metal layer connecting the electrolyte membrane and the lithium negative electrode, achieving uniform deposition of lithium ions and alleviating the problem of poor solid / solid interface contact between the solid electrolyte and the electrode.

[0036] The method for preparing an asymmetric solid electrolyte membrane of the present invention obtains an asymmetric base membrane containing a conductive material facing the lithium metal side by electrostatic spinning, electrostatic spraying or magnetron sputtering, and further obtains an asymmetric solid electrolyte membrane by in-situ polymerization; the electrolyte facing the positive electrode side can also be obtained by one or more methods of solution casting, scraping film, rolling and additive manufacturing, and then the electrolyte with added conductive material facing the negative electrode side is obtained by one or more methods of solution casting, scraping film, rolling and additive manufacturing on the positive electrode side electrolyte. The method is simple, easy to scale up and can be used for large-scale production.

[0037] The solid-state lithium metal battery based on the asymmetric solid electrolyte membrane of the present invention exhibits excellent electrochemical performance. -2 At a current density of , the lithium symmetric battery can operate stably for more than 660 hours. 4 ||Li battery capacity remains at 100mA hg after 650 cycles at 0.5C rate -1 Above, the capacity retention rate is above 70%. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Scanning electron microscope images of (a) PAN electrospinning substrate surface, (b) PAN-CNT electrospinning asymmetric substrate surface, (c) PAN-Ag electrospinning asymmetric substrate surface, (d) PAN@PEDL solid electrolyte membrane surface, (e) PAN-CNT@PEDL asymmetric solid electrolyte membrane surface, and (f) PAN-Ag@PEDL asymmetric solid electrolyte membrane surface prepared in Example 1, Example 2, and Comparative Example 1. (g) Electrochemical impedance spectrum of solid electrolyte membrane at 30°C, (h) Bar graph of ionic conductivity of solid electrolyte membrane and electronic conductivity of electrolyte membrane with CNT added.

[0039] Figure 2 It is a constant current voltage curve diagram of the lithium symmetric battery assembled in Example 1, Example 2 and Comparative Example 1, and the inset is the lithium metal layer at the interface between the PAN-CNT@PEDL asymmetric solid electrolyte membrane and the lithium metal negative electrode.

[0040] Figure 3Solid-state LiFePO assembled from Example 1, Example 2 and Comparative Example 1 4 ||Long cycle performance diagram of Li battery. DETAILED DESCRIPTION

[0041] The specific experimental scheme of the present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to the examples listed. Unless otherwise specified, the methods described are all conventional methods, and the raw materials and instruments used can be purchased on the market.

[0042] Example 1

[0043] (1) Preparation of asymmetric PAN-CNT-based membranes

[0044] Polyacrylonitrile (PAN) was dissolved in N,N-dimethylformamide (DMF), and then carbon nanotubes (CNT) were added and stirred at 60°C for 12 h to prepare a uniform and viscous black spinning solution, wherein the mass ratio of PAN:CNT:DMF was 1:0.5:10. The electrospinning machine was used at a voltage of 18 kV and a jet speed of 0.01 mL min -1 The spinning was carried out under the condition of receiving distance of 15 cm to obtain a black spinning membrane. Then, a DMF solution with a PAN concentration of 10% was used to continue electrospinning on the black spinning membrane. The spinning conditions were voltage of 16 kV and injection speed of 0.01 mL min -1 , receiving distance 15cm, and asymmetric PAN-CNT based membrane was obtained. Pure PAN based membrane without CNT.

[0045] (2) Preparation of asymmetric solid electrolyte membrane

[0046] The polymer monomer polyethylene glycol diacrylate PEGDA, plasticizer ethylene carbonate EC and dimethyl carbonate DMC (volume ratio of 1:1), and lithium salt lithium bis(trifluoromethanesulfonyl)imide LiTFSI were mixed and stirred for 4 hours, and the mass ratio of PEGDA, EC / DMC, and LiTFSI was 1:5:1. Then 2,2-azobisisobutyronitrile AIBN was added and mixed evenly, and the mass ratio of PEGDA and AIBN was 1:0.015. The mixture was added dropwise to the asymmetric PAN / CNT-based membrane prepared in step (1), and then heated in an oven at 70°C for polymerization for 2 hours to obtain an asymmetric solid electrolyte membrane, which was recorded as PAN / CNT@PEDL.

[0047] (3) Assembly of solid-state lithium metal batteries

[0048] According to LiFePO 4, the mass ratio of conductive carbon black Super P and polyvinylidene fluoride PVDF is 8:1:1, weighed and placed in a mortar, ground for 20 minutes, added N-methylpyrrolidone NMP and stirred evenly, prepared into a slurry and then coated on aluminum foil, placed in an oven at 70°C for 24 hours, and cut into positive electrode discs. The battery is assembled in an argon atmosphere glove box, and a CR2025 button lithium metal battery is assembled in the order of positive electrode sheet (or lithium metal), PAN-CNT base film, dropwise addition of the above-mentioned liquid in-situ polymerization electrolyte (polyethylene glycol diacrylate PEGDA, ethylene carbonate EC, dimethyl carbonate DMC, bistrifluoromethanesulfonyl imide lithium LiTFSI and 2,2-azobisisobutyronitrile), lithium metal, and nickel foam. After heating and polymerization, a solid lithium metal battery is obtained, in which the side containing CNT faces the lithium metal negative electrode.

[0049] Example 2

[0050] Preparation of asymmetric PAN-Ag based membrane: polyacrylonitrile PAN was dissolved in N, N-dimethylformamide DMF, stirred evenly to prepare spinning solution, and an electrospinning machine was used at a voltage of 16 kV and a spray speed of 0.01 mL min -1 The spinning was carried out under the condition of receiving distance of 15 cm to obtain a white spinning membrane. Then, the ethanol dispersion of silver nanowires was electrostatically sprayed on the white spinning membrane with a voltage of 16 kV and a spraying speed of 0.01 mL min -1 , receiving distance 5cm, to obtain an asymmetric PAN-Ag base film. Other preparation methods are the same as in Example 1, to obtain PAN-Ag@PEDL and its battery.

[0051] Figure 1 Scanning electron microscope images of (a) PAN base membrane surface, (b) PAN-CNT asymmetric base membrane surface, (c) PAN-Ag asymmetric base membrane surface, (d) PAN@PEDL solid electrolyte membrane surface, (e) PAN-CNT@PEDL asymmetric solid electrolyte membrane surface, and (f) PAN-Ag@PEDL asymmetric solid electrolyte membrane surface prepared in Example 1, Example 2, and Comparative Example 1. (g) Electrochemical impedance spectrum of solid electrolyte membrane at 30°C, (h) Bar graph of ionic conductivity of solid electrolyte membrane and electronic conductivity of electrolyte membrane with CNT added. It can be seen that the addition of CNT makes the fiber surface rough, and silver nanowires evenly cover the fiber surface. The surface of the solid electrolyte membrane is flat, and the base membrane is filled with polymer electrolyte. The ionic conductivities of PAN-CNT@PEDL, PAN-Ag@PEDL, and PAN@PEDL calculated from the impedance spectrum are 3.48, 2.72, and 2.36 mS cm, respectively. -1 The electronic conductivity of the electrolyte membrane with CNT added is 7.24×10 -3 mxD– 1 .

[0052] Figure 2 It can be seen that at 0.2 mA cm -2 At a current density of , the lithium symmetric battery assembled in Example 1 operates stably for more than 630 h, the lithium symmetric battery assembled in Example 2 operates stably for 439 h, and the comparative example 1 fails after operating for 69 h.

[0053] Figure 3 The solid LiFePO of Example 1 can be obtained 4 ||Li battery capacity remains at 100mA hg after 650 cycles at 0.5C rate -1 Above, the capacity retention rate is above 70%.

[0054] The asymmetric solid electrolyte membrane provided by the present invention promotes lithium ion dissociation and improves ion conductivity, while also guiding lithium ions to be uniformly deposited on a single side of the solid electrolyte membrane that conducts ions and electrons and at its interface with the lithium metal negative electrode, thereby improving the problem of lithium dendrite growth and improving the electrochemical performance of the solid electrolyte membrane lithium metal battery.

[0055] Finally, it should be noted that the above embodiment is only one of the implementation methods of the present invention and cannot be understood as limiting the scope of the present invention. Without departing from the scope of the present invention, any equivalent replacement or modification of the present invention shall not depart from the technical solution of the present invention and shall still fall within the protection scope of the present invention.

Claims

1. An asymmetric solid electrolyte membrane that conducts ions / ions and electrons, characterized in that: The side facing the positive electrode includes an ion-conducting electrolyte, and the side facing the negative electrode includes an electrolyte that conducts both ions and electrons with the addition of an electronically conductive material.

2. An ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane as claimed in claim 1, characterized in that: The conductive material includes one or more of carbon nanotubes, silver nanowires, silver nanoparticles, copper nanowires, copper particles and silver-copper alloys.

3. An ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane as claimed in claim 1, characterized in that: It comprises an asymmetric base membrane, wherein the side of the asymmetric base membrane facing the positive electrode comprises a polymer or an electrolyte, and the side facing the lithium metal negative electrode comprises a mixture of a conductive material and a polymer or a conductive material; the asymmetric base membrane is filled with a polymer electrolyte, and the polymer electrolyte contains a plasticizer and a lithium salt.

4. An ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane as claimed in claim 3, characterized in that: The polymer includes one or more of polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride, polyimide, polyetherimide, polyvinyl alcohol, polyvinyl pyrrolidone, polymethyl methacrylate and polyvinyl chloride; and / or The polymer electrolyte is obtained by polymerizing a polymer monomer that conducts lithium ions and mixes a plasticizer and a dissolved lithium salt; and / or The mass ratio of the conductive material to the polymer facing the lithium metal negative electrode side is 0.0001:1 to 1:

0.

5. A method for preparing the ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane according to claim 1, characterized in that: The electrolyte facing the positive electrode side is obtained by one or more methods selected from solution casting, scraping film, rolling and additive manufacturing; the electrolyte with added conductive material facing the negative electrode side is obtained by one or more methods selected from solution casting, scraping film, rolling and additive manufacturing.

6. A method for preparing the ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane according to claim 3, characterized in that: The steps include: (1) Preparation of asymmetric base membrane The conductive material, polymer and solvent are heated, mixed and stirred to form a uniform and viscous spinning solution, and electrostatic spinning is performed on the polymer membrane or electrolyte membrane to obtain a spinning membrane with conductive material added, thereby obtaining an asymmetric base membrane with single-side conductivity; or the conductive material is electrosprayed on one side of the polymer membrane or electrolyte membrane by electrostatic spraying or magnetron sputtering to obtain an asymmetric base membrane with single-side conductivity; (2) Preparation of asymmetric solid electrolyte membrane The lithium salt is dissolved in the polymer monomer and the plasticizer, and the polymerization initiator is added and stirred evenly, and then the mixture is dripped onto the asymmetric base membrane prepared in step (1), and then the base membrane is transferred into an oven for heating and polymerization to obtain the asymmetric solid electrolyte membrane.

7. The method for preparing an ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane according to claim 5 or 6, characterized in that: The mass percentage of the conductive material in the spinning solution, the electrostatic spray solution or the electrolyte facing the negative electrode side is 0.1% to 99.9%.

8. The method for preparing an ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane according to claim 6, characterized in that: In step (2), the mass ratio of the polymer monomer to the lithium salt is 0.01:1 to 100:1; the mass ratio of the plasticizer to the polymer monomer is 0.001:1 to 100:1; and the mass of the polymerization initiator is 0.01 to 100% of the mass of the polymer monomer.

9. The method for preparing an ion-conducting / ion-and-electron-conducting asymmetric solid electrolyte membrane according to claim 6, characterized in that: The mixing and stirring time in step (1) is 1 to 48 hours, and the heating temperature is 30 to 100° C.; and / or, In step (2), the polymerization temperature is 20 to 200° C., and the polymerization time is 0.01 to 48 hours.

10. A solid-state lithium metal battery, characterized in that It comprises a positive electrode, a negative electrode and a solid electrolyte membrane, and is characterized in that the solid electrolyte membrane is the ion-conducting / ion-conducting and electron-conducting asymmetric solid electrolyte membrane as claimed in claim 1 or 3.

Citation Information

Cited By

  • A solid-state battery and its composite electrolyte, preparation and application

    CN120357039B

  • Multi-Layer Self-Healing Solid Electrolyte for All-Solid-State Batteries and All-Solid-State Battery Using the Same

    KR102989524B1